Предмет: Алгебра,
автор: kika000009
Здравствуйте, не могли бы Вы объяснить как это решается?
Из формулы T=3h/b+u выразить h.
Ответы
Автор ответа:
0
T = 3h/b + u
3h/b = T - u
3h = b(T - u)
h = 1/3 * (b(T-u))
3h/b = T - u
3h = b(T - u)
h = 1/3 * (b(T-u))
Автор ответа:
0
Большое спасибо!
Автор ответа:
0
Не за что..))
Похожие вопросы
Предмет: Математика,
автор: dilaraabdurahimova0
Предмет: Литература,
автор: Annaskiba208
Предмет: Геометрия,
автор: ameba1obuknovennai
Предмет: Алгебра,
автор: 1996sasha
Предмет: Литература,
автор: luhan1234